2022
DOI: 10.1155/2022/4766992
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis and Functional Characteristics of Differential Expression of N6-Methyladenosine Methylation Modification in the Whole Transcriptome of Rheumatoid Arthritis

Abstract: N6-methyladenosine (m6A) modification is the most prevalent chemical modification in eukaryotic mRNA and is associated with the development of various immune diseases. However, the role of m6A methylation in rheumatoid arthritis (RA) development is unclear. We preliminarily explored the role of m6A methylation-related mRNAs in RA for its clinical application. The discovery of m6A methylation-modifying genes in this study may provide a fresh perspective on the development of drugs for RA treatment. High-through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…[ 66 ] In RA, DNA methylation changes in immune-related genes such as HLA-DRB1 and PTPN22 are closely associated with disease risk and clinical manifestations. [ 67 , 68 ] Moreover, abnormal regulation of gene methylation is also associated with the development and pathological features of autoimmune diseases such as SLE and Sjögren’s syndrome. [ 69 , 70 ] Additionally, the abnormal expression of certain microRNAs is linked to the occurrence and progression of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 66 ] In RA, DNA methylation changes in immune-related genes such as HLA-DRB1 and PTPN22 are closely associated with disease risk and clinical manifestations. [ 67 , 68 ] Moreover, abnormal regulation of gene methylation is also associated with the development and pathological features of autoimmune diseases such as SLE and Sjögren’s syndrome. [ 69 , 70 ] Additionally, the abnormal expression of certain microRNAs is linked to the occurrence and progression of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…m6A methylation modification is also crucial in RA development [14,42,43]. m6A methylation is an abundant internal modification on RNA [44][45][46]. The binding protein can recognize the m6A methylation site of mRNA, affecting the abundance and function of mRNAs with m6A modification sites.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of m6A modified significantly transcriptor-rich inflammatory signaling pathway was evaluated through animal experiments, and it was found that the differential expression of m6A gene is closely related to macrophage activation and inflammatory processes such as MAPK, PI3K-Akt and JAK-STAT signaling pathways. Some genes enriched in the PI3K-Akt and MAPK pathways are mostly inhibitors of the corresponding pathways, including PTEN, ASPM and SHCBP1 [ 46 , 47 ]. Through data mining, Liu et al [ 48 ] demonstrated that the m6A-RNA methylation regulators (m6A-RMRs) were more differentially expressed in rheumatoid arthritis (RA) and autoimmune skin diseases than those in other autoimmune diseases.…”
Section: M6a Methylation In Ramentioning
confidence: 99%